The Threat of International Terrorism in the Central Asian and Afghan Direction: Key Factors - A. A. Kazantsev (Международная аналитика, 2016)
The article deals with analysis of the factors affecting the growth of terrorist threat to Russia from Central Asian and Afghan direction. The author of the paper defines and analyzes the following key factors. 1. Threat of return of Central Asian terrorist fighters from the Middle East and other conflict zones of the world. 2. Serious growth of instability in Afghanistan that provokes the threat of incursions of terrorists into the countries of Central Asia. 3. Critical connection of some external and internal threats to Central Asian security, which includes: state fragility, drug transportation from Afghanistan to Russia through the Northern Route, high corruption, demodernization of socio-economic sphere, serious interstate conflicts between Central Asian states themselves as well as between the key world powers involved into Central Asian affairs. 4. Serious potential of development of religious extremism in Tajikistan, Turkmenistan and Uzbekistan, as well as in some regions of Kazakhstan and Kyrgyzstan.